Retraction Note: A photon thermal diode - Zhen Chen (Nature Portfolio, 2017)
Nature Communications 5: Article number: 5446 (2014); Published: 17 November 2014; Updated: 21 August 2017 Because two of its three major findings have been invalidated, the authors wish to retract this Article1. Budaev2 correctly identifies a fundamental symmetry error in the way the ‘inelastic thermal collimation’ was configured in several crucial experiments of ref.